Three-Dimensional Analysis of Choroidal Vessels in the Eyes of Patients With Unilateral BRVO - Chen, Lulu; Yuan, Mingzhen; Sun, Lu; Chen, Youxin (Frontiers in Medicine, 2022)
Purpose To investigate the three-dimensional analysis of choroidal vascular changes in eyes with monocular branch retinal vein occlusion (BRVO) using swept-source optical coherence tomography (SS-OCT). Methods 22 unilateral BRVO patients with superior-temporal branch retinal vein occlusion and 27 healthy eyes were analyzed retrospectively. OCT and OCT angiography (OCTA) images of 12*12mm centered on the foveal of each eye were analyzed. Three-dimensional choroidal vascularity index (CVI), choroidal thickness, and choriocapillaris density were compared among BRVO eyes, fellow eyes, and healthy control eyes. En face CVI maps in BRVO eyes were generated to analyze the dilatation pattern of choroidal vessels. Results CVI values in a few 1*1mm grids in the non-affected hemi side were higher in BRVO eyes compared with the fellow eyes and control eyes (p<0.05). Choriocapillaris density decreased in both BRVO eyes and fellow eyes compared with normal eyes while choriocapillaris density was higher in a few grids in the non-affected hemi side in BRVO eyes compared with fellow eyes (p<0.05). Choroidal dilatation pattern was categorized into four types and inferior choroidal dilatation and posterior pole choroidal dilatation were the major types. Conclusions Three-dimensional CVI tended to increase in non-affected hemi side and choroidal vessels tended to dilate in adjacent areas in BRVO eyes. Choriocapillaris density decreased in both eyes of monocular BRVO patients. The choroidal changes suggested that choroidal redistribution occurred in BRVO.